1993
DOI: 10.1111/j.1365-2958.1993.tb00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel determinant (comA) essential for natural transformation competence in Neisseria gonorrhoeae and the effect of a comA defect on pilin variation

Abstract: A novel genetic determinant (comA) has been identified and found to be required for the transformation of piliated Neisseria gonorrhoeae. Mutants in comA of strain MS11 grow normally and are DNA-uptake proficient but blocked in the translocation of DNA into the cytoplasm. Here we show by site-specific mutagenesis and genetic complementation that only one of two open reading frames identified in comA is essential for competence: it encodes a protein (ComA) with a predicted size of 74 kDa. The comA gene maps ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 58 publications
2
75
2
Order By: Relevance
“…ComA is essential for transport of DNA through the cytoplasmic membrane but does not affect DNA uptake into the periplasm (28). We found that the force-dependent velocity was independent of comA ( Fig.…”
Section: The Velocity Vs Force Relationship Is In Agreement With Amentioning
confidence: 51%
See 1 more Smart Citation
“…ComA is essential for transport of DNA through the cytoplasmic membrane but does not affect DNA uptake into the periplasm (28). We found that the force-dependent velocity was independent of comA ( Fig.…”
Section: The Velocity Vs Force Relationship Is In Agreement With Amentioning
confidence: 51%
“…In N. gonorrhoeae and other competent species, transport through the outer membrane is uncoupled from transport through the inner membrane (25)(26)(27). Single-stranded DNA is transported through a pore formed by ComA through the inner membrane (28). The probability of DNA uptake is strongly enhanced by the presence of the DNA uptake sequence (DUS) (29).…”
mentioning
confidence: 97%
“…In addition to beta-lactamases, a number of other proteins are known to contain the metallobeta-lactamase domain, including thiolesterases that belong to the glyoxalase II family and catalyze the hydrolysis of S-Dlactoyl-glutathione to generate glutathione and D-lactic acid (2). In Neisseria gonorrhoeae, a competence protein required for natural transformation likely is a transporter involved in DNA uptake and also has this domain (10). If vicX encodes a DNA transporter similar to that in N. gonorrhoeae, we would expect a vicX null mutant to show decreased transformability.…”
Section: Discussionmentioning
confidence: 99%
“…While the first step requires functional pili (15), the second step depends on comA and is strongly facilitated by exbB (17). The polytopic membrane protein ComA and its orthologs are key components of the DNA transmembrane translocation machinery of other transformable organisms, like N. gonorrhoeae (13), H. influenzae (9), B. subtilis (19), and S. pneumoniae (30). ComA protein is thought to form the pore through which a single strand derived from duplex transforming DNA by degradation of one strand by an unknown DNase reaches the cytoplasm (12).…”
mentioning
confidence: 99%